Effects of Light Spectra on Morphology, Gaseous Exchange, and Antioxidant Capacity of Industrial Hemp - Cheng, Xia; Wang, Rong; Liu, Xingzhu; Zhou, Lijuan; Dong, Minghua; Rehman, Muzammal; Fahad, Shah; Liu, Lijun; Deng, Gang (Frontiers in Plant Science, 2022)
One of the most important growth factors in cannabis cultivation is light which plays a big role in its successful growth. However, understanding that how light controls the industrial hemp growth and development is poor and needs advance research. Therefore, a pot study was conducted to explore the effects of different colors of light i.e., white light (WL), blue light (BL), red light (RL), and 50% red with 50% blue mix light (RBL) on morphology, gaseous exchange and antioxidant capacity of industrial hemp. Compared with WL, BL significantly uphold hemp growth in the form of fresh biomass, dry biomass, leaves number per plant, stem diameter, root length and chlorophyll content. In addition BL promoted net photosynthesis, stomatal conductance and transpiration while, reduces the lipid peroxidation and superoxide dismutase and peroxidase activities. However, RL and RBL significantly reduced the plant biomass, gas-exchange parameters with enhanced antioxidant enzymes activities. Thus blue light is useful for large scale sustainable production of Industrial hemp.